Traditional excluding forces: A review of the quantitative literature on the economic situation of indigenous peoples, afro-descendants, and people living with disability - Néstor Gandelman; Hugo \~Nopo; Laura Ripani (Inter-American Development Bank, Research Department, 2007)
Unequal income distribution in Latin America and the Caribbean is linked to unequal distributions of (human and physical) assets and differential access to markets and services. These circumstances, and the accompanying social tensions, need to be understood in terms of traditional fragmenting forces; the sectors of the population who experience unfavorable outcomes are also recognized by characteristics such as ethnicity, race, gender and physical disability. In addition to reviewing the general literature on social exclusion, this paper surveys several more specific topics: i) relative deprivation (in land and housing, physical infrastructure, health and income); ii) labor market issues, including access to labor markets in general, as well as informality, segregation and discrimination; iii) the transaction points of political representation, social protection and violence; and iv) areas where analysis remains weak and avenues for further research in the region.
Keywords: 330; Discrimination; Social exclusion; Latin America and the Caribbean; Minderheit; Indigene Völker; Schwarze; Behinderte; Lebensstandard; Soziale Lage; Lateinamerika